(untitled) (Global Journal of Science Frontier Research, 2018)
In the article the electrical and current self-induction of radio-technical elements and chains is examined and it is shown that such elements can present the effective resistance, which depends on the time. Is introduced the concept of parametric self-induction. On the basis of the concepts indicated is obtained the wave equation for the long lines, which gives the possibility to establish the velocity of propagation of the front of stress with the connection to the line of dc power supply. The concept of the potential and kinetic flows of charges is introduced.